Antilisterial effect of two bioprotective cultures in a model system of Iberian chorizo fermentation. (8th October 2013) - Ortiz, Sagrario; López, Victoria; Garriga, Margarita; Martínez‐Suárez, Joaquín V.
Summary This study reports the different effects of two bioprotective cultures on the growth of different Listeria monocytogenes strains by a rapid assay simulating the first stage of Iberian chorizo fermentation. Ground pork with or without protective cultures was inoculated with L. monocytogenes and incubated under two different conditions simulating the traditional, slow fermentation temperature (7 °C, 1 day) and a high, fast fermentation temperature (20 °C, 1 day), followed in both cases by storage at 7 °C for 13 days. Both bioprotective cultures reduced the growth of L. monocytogenes by at least 2 log CFU g−1 at the end of both incubation periods compared with a noninoculated culture control lot. The best results were obtained with the strain Lactobacillus sakei CTC494, which exerted a bactericidal effect on L. monocytogenes under both conditions assayed, achieving a 5.4‐log reduction after 14 days compared with the control when the initial temperature was 20 °C.